Implementation of Project-Based Islamic Education to Strengthen the Pancasila Student Profile (P5) - Fahmi; La Aba; Ni'ma M. Alhabsyi; Tuharso (Journal of Practice Learning and Educational Development, 2026)
This study describes the implementation of Project-Based Learning (PjBL) in Islamic Religious Education (PAI) integrated with P5 at SMK Negeri 1 Limboto and identifies its challenges. Using a qualitative descriptive approach, the results show that teachers' strategies focus on Faith and Piety, Global Diversity, and Mutual Cooperation dimensions. Implementation is realized through contextual projects such as social service and digital literacy, successfully shifting the learning paradigm from a textual model to an experiential approach. However, structural obstacles including time constraints and administrative burdens, alongside cultural challenges like the persistent teacher-centered mindset, remain significant. Weak conflict management among students also hinders optimal collaboration. The study recommends flexible academic scheduling and strengthening the teacher's role as a facilitator to ensure substantive character internalization. This synergy is crucial for vocational students to balance technical competence with strong moral integrity in the professional world.